2009
DOI: 10.1364/ol.34.000740
|View full text |Cite
|
Sign up to set email alerts
|

Microjoule pulse energy from a chirped-pulse Ti:sapphire oscillator with cavity dumping

Abstract: We demonstrate a chirped-pulse Ti:sapphire laser oscillator with both Kerr-lens and semiconductor- saturable-absorber-mirror-assisted mode locking generating 1.1 microJ pulses at 1 MHz pulse repetition rate. The pulses are coupled out of the laser cavity by means of an acousto-optical cavity dumper, have a spectral width that supports a Fourier limit of 74 fs, and currently have a chirped-pulse duration of 5 ps. After compressing the pulses, this laser will be an ideal tool for efficient high-harmonic generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The next step was an observation that a chirped-pulse oscillator allows the pulse energy scaling (Apolonski et al (2000); Fernandez et al (2004)). The result was a swift rise of the pulse energy from a Ti:sapphire chirped-pulse oscillator (Fernández et al (2007); Naumov et al (2005); Siegel et al (2009)). The decisive steps were the cavity period T rep growth and the positive dispersion control within a broad spectral range (Pervak et al (2008)).…”
Section: Experimental Realizations Of Solid-state Chirped-pulse Oscilmentioning
confidence: 99%
“…The next step was an observation that a chirped-pulse oscillator allows the pulse energy scaling (Apolonski et al (2000); Fernandez et al (2004)). The result was a swift rise of the pulse energy from a Ti:sapphire chirped-pulse oscillator (Fernández et al (2007); Naumov et al (2005); Siegel et al (2009)). The decisive steps were the cavity period T rep growth and the positive dispersion control within a broad spectral range (Pervak et al (2008)).…”
Section: Experimental Realizations Of Solid-state Chirped-pulse Oscilmentioning
confidence: 99%
“…Up to 1.7 MHz has been already achieved with a regenerative Ti:Sapphire amplifier at a shorter wavelength of 800 nm [12]. Complementary to the increase in the repetition rate of regenerative amplifiers, a fast evolution of mode-locked ultra-short pulse oscillators [13,14] with reduced repetition rate down to 1 MHz and with higher single pulse energies up to the µJ-level took place. Recently, a Gd:YVO 4 cavity dumped oscillator with 1 MHz repetition rate using an RTP Pockels cell was reported [15].…”
Section: Introductionmentioning
confidence: 99%
“…Dissipative solitons (DS) mode-locked lasers, which are generally occurred in net positive intra-cavity dispersion or all normal dispersion regions, have attracted much attention in recent years due to the large capacity in pulse energy and difficulty in soliton splitting. Characterized by strongly chirped pulse and shaped spectrum with steep edge, the DS modelocking operations have been demonstrated in various lasers such as chirped pulse oscillators [1][2][3][4][5] and all normal dispersion Yb or Er doped fiber lasers [6][7][8][9]. Recently, Tan et al reported the evidence of DS in an Yb:CaYAlO 4 (Yb:CYA) laser for the first time [10], the result has implied that the DS operation can exist in the positive cavity dispersion modelocking regime of the Yb doped solid state lasers.…”
Section: Introductionmentioning
confidence: 99%